Computer networking : a top-down approach featuring the Internet - Kurose, James F. (Pearson/Addison Wesley, 2005)
"Revised to reflect the rapid changes in the field of networking, Computer Networking provides a top-down approach to this study by beginning with application-level protocols and then working down the protocol stack. An early emphasis is placed on application-layer paradigms and application programming interfaces to allow readers to get their "hands dirty" with protocols and networking concepts in the context of applications they will use in the industry. Networking today is much more (and far more interesting) than standards specifying message formats and protocol behaviors. Professors Kurose and Ross focus on describing emerging principles in a lively and engaging manner and then illustrate these principles with examples drawn from Internet architecture."--BOOK JACKET.